Producto de apoyo en el tratamiento terapéutico de patologías biomecánicas del antebrazo causadas por actividades laborales - Naranjo Hidalgo, Joceline Salomé (2024)
The present integrative project focuses on occupational activities as a potential cause or exacerbating factor for forearm pathologies. Common risk factors for employees include wrist deviation postures, prolonged exposure to repetitive movements without rest, and inadequate ergonomics in work environments. Symptoms may result from acquired issues, working conditions, and personal factors, all contributing to forearm pathology development. These conditions impact daily activities, causing fatigue, pain, loss of motor abilities, and emotional frustration. Consequently, this study proposes the design of a therapeutic support product to address forearm pathologies and alleviate associated symptoms in both personal and professional aspects of employees' lives. The Physical Therapy Laboratory at the Technical University of Ambato oversees this project, providing physical rehabilitation to employees across various faculties and campuses. The primary goal is to design a product that aids in the treatment of forearm pathologies caused by occupational activities, with the aim of facilitating a speedy recovery and the successful return to work for employees.